2020
DOI: 10.3389/fnut.2020.604283
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Ameliorates Gut Microbiota Dysbiosis in Lupus-Like Mice

Abstract: Gut microbiota has a strong influence on the onset and development of systemic lupus erythematosus (SLE), and several studies have demonstrated the effectiveness of microbiota-derived butyrate to ameliorate SLE. However, the roles of butyrate on gut microbiota in SLE are not understood. Using MRL/lpr lupus-prone mice, we examined gut microbiota profiles after butyrate treatment by 16S rRNA sequencing. Alterations in intestinal microbiome in mice with lupus-like disease were mainly characterized by a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
(53 reference statements)
0
32
0
1
Order By: Relevance
“…Stool samples from mice were collected by stimulating the anus and immediately frozen in a − 80 °C refrigerator. Fecal SCFAs were detected by gas chromatography–mass spectrometry (GC–MS) as previously described (He et al 2020 ; Wang et al 2019 ). Stool DNA extraction was performed with the Qiagen DNA Stool MiniKit (Qiagen, Cat No.…”
Section: Methodsmentioning
confidence: 99%
“…Stool samples from mice were collected by stimulating the anus and immediately frozen in a − 80 °C refrigerator. Fecal SCFAs were detected by gas chromatography–mass spectrometry (GC–MS) as previously described (He et al 2020 ; Wang et al 2019 ). Stool DNA extraction was performed with the Qiagen DNA Stool MiniKit (Qiagen, Cat No.…”
Section: Methodsmentioning
confidence: 99%
“…Gut microbiota dysbiosis strongly influences the onset and development of systemic lupus erythematosus (SLE). Several studies have demonstrated microbiota-derived butyrate’s effectiveness in ameliorating SLE ( He et al, 2020 ). This study used MRL/lpr lupus-prone mice to examine the roles of butyrate on gut microbiota in SLE ( He et al, 2020 ).…”
Section: Results and Context Of Included Studiesmentioning
confidence: 99%
“…Romboutsia, Odoribacter, and Turicibacter were all also relatively decreased in HLA-DR3. Although these bacteria have not been studied with relation to EAE or MS, they have been associated with various inflammatory diseases (69,70).…”
Section: Discussionmentioning
confidence: 99%